Sublethal Paraquat Confers Multidrug Tolerance in Pseudomonas aeruginosa by Inducing Superoxide Dismutase Activity and Lowering Envelope Permeability - Martins, Dorival; McKay, Geoffrey A.; English, Ann M.; Nguyen, Dao (Frontiers in Microbiology, 2020)
Stressors and environmental cues shape the physiological state of bacteria, and thus how they subsequently respond to antibiotic toxicity. To understand how superoxide stress can modulate survival to bactericidal antibiotics, we examined the effect of intracellular superoxide generators, paraquat and menadione, on stationary-phase antibiotic tolerance of the opportunistic pathogen, Pseudomonas aeruginosa. We tested how pre-challenge with sublethal paraquat and menadione levels alters the tolerance to ofloxacin and meropenem in wild-type P. aeruginosa and mutants lacking superoxide dismutase (SOD) activity (sodAB), the paraquat responsive regulator soxR, (p)ppGpp signaling (ΔrelA spoT mutant), or the alternative sigma factor rpoS. We confirmed that loss of SOD activity impairs ofloxacin and meropenem tolerance in stationary phase cells, and found that sublethal superoxide generators induce drug tolerance by stimulating SOD activity. This response is rapid, requires de novo protein synthesis, and is RpoS-dependent but does not require (p)ppGpp signaling nor SoxR. We further showed that pre-challenge with sublethal paraquat induces a SOD-dependent reduction in cell-envelope permeability and ofloxacin penetration. Our results highlight a novel mechanism of hormetic protection by superoxide generators, which may have important implications for stress-induced antibiotic tolerance in P. aeruginosa cells.